Canine atopic dermatitis attenuated by mesenchymal stem cells - Ramos, Fernanda de Oliveira; Malard, Patricia Furtado; Brunel, Hilana dos Santos Sena; Paludo, Giane Regina; Castro, Marcio Botelho de; da Silva, Paulo Henrique Sampaio; Vianna, Andre Rodrigues da Cunha Barreto; Lima, Eduardo Mauricio Mendes de (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: To evaluate the use of mesenchymal stem cells (MSCs) in the attenuation of canine atopic dermatitis (AD). Materials and methods: Sixteen dogs were selected and divided into three groups, mild, moderate, and severe, according to the Canine Atopic Dermatitis Extent and Severity Index (CADESI-4). They were evaluated for 82 days. The protocol recommended in this experiment was to inject 2 × 106/kg bodyweight of MSC’s in all groups by the intravenous route with intervals of applications of 21 days. The degree of pruritus was evaluated by examining the visual analog scale, the CADESI-4, the histopathology of the skin, hematological and biochemical parameters, the pyogenic effect of MSCs, and the thickness of the epidermis. Results: There was a significant difference in the reduction of epidermal thickness in the moderate and severe groups. Hematological, biochemical, and body temperature parameters remained within normal limits for the species with no side effects Conclusion: MSCs attenuated the clinical signs of AD. J. Adv. Vet. Anim. Res., 7(3): 554-565, Sep 2020 http://doi.org/10.5455/javar.2020.g453